2006
DOI: 10.1083/jcb.200511010
|View full text |Cite
|
Sign up to set email alerts
|

Stu2p binds tubulin and undergoes an open-to-closed conformational change

Abstract: Stu2p from budding yeast belongs to the conserved Dis1/XMAP215 family of microtubule-associated proteins (MAPs). The common feature of proteins in this family is the presence of HEAT repeat–containing TOG domains near the NH2 terminus. We have investigated the functions of the two TOG domains of Stu2p in vivo and in vitro. Our data suggest that Stu2p regulates microtubule dynamics through two separate activities. First, Stu2p binds to a single free tubulin heterodimer through its first TOG domain. A large conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
211
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(229 citation statements)
references
References 49 publications
17
211
1
Order By: Relevance
“…We asked whether Stu2⌬N localization is similar to endogenous Stu2 by tagging Stu2⌬N with venus fluorescent protein (VFP) (which still retains its spc24-9 HU rescue activity) and endogenous Stu2 with cyan fluorescent protein (CFP). Indeed, we found that Stu2⌬N-VFP localization overlapped with Stu2-CFP in both wild-type and spc24-9 mutants in log phase or HUtreated cells, consistent with previous data, demonstrating that Stu2⌬TOG1-GFP still binds MT plus ends (Supplemental Figure 2; Al-Bassam et al, 2006). To test whether depletion of Stu2 activity by using another mutant form of Stu2 is also capable of preventing spindle expansion in spc24-9 cells, we combined spc24-9 with the stu2-10 temperature-sensitive (Ts) mutation (Severin et al, 2001) and tested the double mutant for separation of nuclei upon HU treatment.…”
Section: Hcs Rescue Occurs Through Restraining Spindle Expansionsupporting
confidence: 78%
See 1 more Smart Citation
“…We asked whether Stu2⌬N localization is similar to endogenous Stu2 by tagging Stu2⌬N with venus fluorescent protein (VFP) (which still retains its spc24-9 HU rescue activity) and endogenous Stu2 with cyan fluorescent protein (CFP). Indeed, we found that Stu2⌬N-VFP localization overlapped with Stu2-CFP in both wild-type and spc24-9 mutants in log phase or HUtreated cells, consistent with previous data, demonstrating that Stu2⌬TOG1-GFP still binds MT plus ends (Supplemental Figure 2; Al-Bassam et al, 2006). To test whether depletion of Stu2 activity by using another mutant form of Stu2 is also capable of preventing spindle expansion in spc24-9 cells, we combined spc24-9 with the stu2-10 temperature-sensitive (Ts) mutation (Severin et al, 2001) and tested the double mutant for separation of nuclei upon HU treatment.…”
Section: Hcs Rescue Occurs Through Restraining Spindle Expansionsupporting
confidence: 78%
“…We propose that overexpression of STU2⌬N rescues spc24-9 HU lethality by restraining MT dynamics induced by mislocalization of Stu2. STU2⌬N lacks the N-terminal TOG1 domain that binds tubulin heterodimers but retains the TOG2 domain that binds MT plus ends (Al-Bassam et al, 2006). Previous studies have shown that Stu2 lacking its TOG1 domain binds MT plus ends but cannot promote plus-end MT growth, suggesting that STU2⌬N inhibits spc24-9 HU spindle expansion via the same mechanism (Al-Bassam et al, 2006).…”
mentioning
confidence: 99%
“…Acquired or inherited mutation in genes of the spindle checkpoint have been linked to several cancers (30)(31)(32)(33). For example, insertions and point mutations in both the kinetochore localization domains and the kinase domains of Bub1 and BubR1 have been found in leukemias and lymphomas (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Sedimentation equilibrium measurements of Mad3 and Mad3-Bub3 were made at 4°C in an analytical ultracentrifuge (Optima XLA; Beckman Coulter, Fullerton, CA) as described in ref. 30. Mad3 was prepared in 25 mM Bis-Tris-Pro, pH 6.5/250 mM NaCl/1 mM 2-mercaptoethanol, and Mad3-Bub3 was prepared in 10 mM Tris, pH 8.0/250 mM NaCl/1 mM 2-mercaptoethanol.…”
Section: Expression and Purification Of Saccharomyces Cerevisiae Checmentioning
confidence: 99%
“…6). This phenotype is not common, since most of the mutants of factors aVecting microtubules such as Bim1, Bik1 and Stu2 are more sensitive to such drugs (Al-Bassam et al 2006;Berlin et al 1990;Schwartz et al 1997;Winsor and Schiebel 1997).…”
Section: Discussionmentioning
confidence: 99%